Miniaturized 3D fibrous scaffold on stereolithography-printed microfluidic perfusion culture - Ng, Feng Lin (2019)
Cells cultured on 2-Dimensional (2D) and 3-Dimensional (3D) substrates generally display significant differences in terms of cell shape, proliferation, morphogenesis and differentiation. While 3D substrates provide better interaction with cell-cell, cell-ECM or cell-soluble factors, tissue construct greater than 200 µm will experience involuntary cell death, e.g. necrosis within the construct. Such an involuntary cell death can be prevented by providing sufficient perfusion through the construct.